Islam And Positive Psychology: Developing Mental Resilience Based On Religious Teachings - Muhammad Arsy Wafiq; Jenuri, Jenuri (Penerbit Hellow Pustaka, 2025)
This study aims to examine the concept of mental resilience from an Islamic perspective and positive psychology, and how both can contribute to strengthening an individual's mental resilience in facing life's challenges. The research method used is a literature study, by collecting and analyzing relevant literature, such as books, journal articles, and trusted online sources. This study identifies various views and research results on mental resilience, and combines the concept of mental resilience in Islam and positive psychology. The results of the study indicate that mental resilience, both from an Islamic perspective and positive psychology, has an important role in helping individuals to remain steadfast and optimistic in facing various life difficulties. In addition, Islamic values, such as tawakal, patience, and gratitude, and positive psychology principles, such as optimism and self-strength, can complement each other in strengthening mental resilience.